Anatoly Vasiliev’s Theatre. Semiology of Continuity and the Way to a New Type of Theatrical System - A. I. Perevalov (Дискурс)
Introduction. The article provides a general description of Anatoly Vasiliev’s theatrical method, discussing the essence of methodological and philosophical breakthroughs in the future of Russian and world theaters, and, in this context, the continuity of the main tenets of Stanislavsky’s system.Methodology and sources. The article compares two theatrical concepts, two methodological, philosophical, and historical approaches of Russian and World Theatres: Stanislavski’s system and Vasiliev’s method. It determines the semiology of continuity and features of a new approach to the development of dramatic art.Results and discussion. The article highlights the elements of the Stanislavsky system present in Anatoly Vasiliev’s method, aiming to derive an algorithm for utilizing new opportunities based on established systems and techniques for training modern actors. The article's conclusions are drawn from five years of experience (since 1988) with the Vasiliev method, gained through direct contact with the master while collaborating on texts by Plato, Oscar Wilde, Fyodor Dostoevsky, William Faulkner, Thomas Mann, Erasmus of Rotterdam, and Alexander Pushkin. As the article relies on introspective research followed by epistemological analysis, it maintains a subjective nature. It is the outcome of the author’s experience working within the Anatoly Vasiliev’ s School of Dramatic Art at the GITIS acting and directing course (1988–1993), and years of observation of the method’s evolution in working with Vasiliev's students, students of theater universities, and professional actors both in Russia and abroad.Conclusion. The article does not claim to precisely represent Vasiliev’s ideas and thoughts but rather reflects the author’s journey through the rehearsal process in Vasiliev’s theater, acknowledging the internal changes experienced by the author as an actor, director, and individual within the method. It abstains from making value judgments regarding the Stanislavsky system and Vasiliev’s method, instead highlighting the most distinctive features of the theatrical method, elucidating its philosophy, and emphasizing the unity between the Stanislavsky and Vasiliev systems.